Centre – Periphery Relations Through the Trans-European Motorway in Turkey - Mete Başar Baypinar (European Regional Science Association (ERSA), 2003)
European Spatial Development Perspective aims to decentralise the congestion from the centre of Europe to peripheral countries, by supporting development through urban corridors. ESDP also aims to decrease regional disparities to increase the overall competitiveness. Therefore urban corridors that connect the peripheral countries to European system have to be paid attention, to formulate policies of development in these countries, within harmony to European policies. Such a corridor in Turkey is the Trans – European Motorway (TEM) corridor. TEM, as a part of Trans European Networks (TENs) connects the two most important metropolitan centres of Turkey, Ankara and Istanbul to Europe, over an already existing route. The route also hosts many important industrial plants, universities and is one of the most heavily used inland corridor. This paper tries to analyse whether the development of the corridor is in accordance with the aims of the ESDP and other European Union spatial policies, and if the competitiveness of the centres in the corridor has increased and if centre-periphery disparities have decreased by using provincial level data such as the level of regional specialisation, GDP per capita, labour force, amount of public investment and other indicators, from present to year 1980, the date when Turkey changed its economic strategy and an integration to global system gained more importance.
Keywords: 330